2017
DOI: 10.1007/s11302-017-9594-z
|View full text |Cite|
|
Sign up to set email alerts
|

P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2′,3′-dideoxycytidine

Abstract: The direct neurotoxicity of HIV and neurotoxicity of combination antiretroviral therapy medications both contribute to the development of neuropathic pain. Activation of satellite glial cells (SGCs) in the dorsal root ganglia (DRG) plays a crucial role in mechanical and thermal hyperalgesia. The P2Y 12 receptor expressed in SGCs of the DRG is involved in pain transmission. In this study, we explored the role of the P2Y 12 receptor in neuropathic pain induced by HIV envelope glycoprotein 120 (gp120) combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Mounting evidence suggests that activation of satellite glial cells indeed participate in neuropathic pain. 39 41 Thus, the transient presence of ATF2 in these cells may have a role in neuropathic pain. Our data partially agree with other observations indicating that stimulation of adult DRG neurons by doxorubicin or ultraviolet irradiation ( in vitro ) and axotomy ( in vivo ) induce a rapid (2–24 h) and consistent (3–20 days) down-regulation of ATF2.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that activation of satellite glial cells indeed participate in neuropathic pain. 39 41 Thus, the transient presence of ATF2 in these cells may have a role in neuropathic pain. Our data partially agree with other observations indicating that stimulation of adult DRG neurons by doxorubicin or ultraviolet irradiation ( in vitro ) and axotomy ( in vivo ) induce a rapid (2–24 h) and consistent (3–20 days) down-regulation of ATF2.…”
Section: Discussionmentioning
confidence: 99%
“…73 Another study demonstrated elevated expression of P2X3 protein in DRG in gp120-treated rats that correlated with neuropathic hypersensitivity sensitive to pharmacological antagonism of P2X3. 74,75 Upregulation of DRG expression of P2X7 has also been demonstrated following gp120 treatment. Subsequent treatment with the P2X7 antagonist, brilliant blue G, decreased hyperalgesia and P2X7 expression, and also decreased IL-1β and TNF-α receptor expression while increasing IL-10 in gp120-treated DRG.…”
Section: Mechanisms Of Chronic Pain In Hivmentioning
confidence: 95%
“…P2Y12 antagonism reduces pain by reducing microglial activation and p38 MAPK phosphorylation in a spinal nerve ligation neuropathic pain model (77). Similarly, the expression of P2Y12 receptor in peripheral satellite glia is also related to pain and its antagonism leads to reduced cytokine production and p38 MAPK phosphorylation and higher withdrawal thresholds (78). It has been demonstrated that in platelets activation of P2Y12 receptor occurs in lipid rafts (79,80).…”
Section: P2x and P2y Purinergic Receptorsmentioning
confidence: 99%